Building communities : social networking for academic libraries - Garofalo, Denise A. (Chandos social media series., 2013)
Social media is here to stay. A robust social media campaign can provide academic libraries with a means to showcase library resources, highlight content and events, and attract students to sample what the library has to offer. Building Communities is a handbook to implement social media technologies for academic libraries. It is a guide to planning and implementing a successful social media campaign and evaluating its impact. This title covers: the beginning of social networking in the academic context; how to implement use of social media technologies; and evaluating their use. The final sec.